1997
DOI: 10.1161/01.cir.95.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial Outcome After Catheter Balloon Commissurotomy in Patients With Mitral Stenosis

Abstract: The rates for intermediate-term survival and event-free survival after CBC are very encouraging. Most patients without events were asymptomatic or minimally symptomatic. Thus, in selected patients with mitral stenosis who require an interventional procedure, CBC is the procedure of choice at centers with physicians who have experience and skill in performing this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 48 publications
6
52
0
4
Order By: Relevance
“…Es así como Olmos y cols publicaron el año 1994 en esta revista los datos de 300 VMB realizadas en nuestro medio, confirmando los buenos resultados difundidos en la literatura 9 . Al igual que ésta, existen varias publicaciones internacionales con resultados a mediano plazo 10,11,12,13 , pero sólo unas pocas presentan datos con 10 o más años de seguimiento 14,15,16 . De esta forma, en nuestro conocimiento este trabajo representa el seguimiento más prolongado de una serie nacional de VMB.…”
Section: Discussionunclassified
“…Es así como Olmos y cols publicaron el año 1994 en esta revista los datos de 300 VMB realizadas en nuestro medio, confirmando los buenos resultados difundidos en la literatura 9 . Al igual que ésta, existen varias publicaciones internacionales con resultados a mediano plazo 10,11,12,13 , pero sólo unas pocas presentan datos con 10 o más años de seguimiento 14,15,16 . De esta forma, en nuestro conocimiento este trabajo representa el seguimiento más prolongado de una serie nacional de VMB.…”
Section: Discussionunclassified
“…4,5,7 • There are reductions of MVG, LA (PA wedge), and PA pressures, and an increase of CO; 60% of patients improve to New York Heart Association functional class (NYHA FC) I and 30% to NYHA FC II, 4,7 which has been objectively documented by exercise tests. 7 • A good immediate result is obtained in Ϸ89% of patients. 4 • A closed mitral commissurotomy in a nonrandomized study in the 1950s and 1960s has shown an improved survival in symptomatic patients (NYHA FC II and III-IV) when compared with medical therapy.…”
Section: Catheter Balloon Commissurotomymentioning
confidence: 92%
“…5 • Follow-up to 10 years after CBC shows very good eventfree survival ( Figure 3A). 4 There were no deaths in up to 7 years of follow-up, and the event rate (MVR or repeat CBC) was 10% ( Figure 3B) 7 in patients who after CBC had MVA Ն1.5cm 2 and mean PA wedge pressure Յ18 mm Hg.…”
Section: Catheter Balloon Commissurotomymentioning
confidence: 97%
See 1 more Smart Citation
“…Although there are numerous predictors of late events following the procedure -age, functional class IV, previous surgical commissurotomy, moderate to severe mitral deficit, echo score > 8, severe mitral deficit following dilatation and increased pressure in the pulmonary artery after dilatation, small valve area after the procedure 2 ), non-sinus rhythm, valve calcification on fluoroscopy, increased LA pressure, increased transvalvular gradient [9][10][11][12][13][14][15] ; there are no details in the literature about changes of P wave in the electrocardiogram performed after the mitral valvuloplasty in patients with mitral stenosis and left atrial enlargement, and there is even less understanding about the meaning of these changes at late follow-up after the percutaneous intervention.…”
Section: Resultsmentioning
confidence: 99%